PENGARUH PRODUKSI KEDELAI, HARGA KEDELAI IMPOR, DAN NILAI TUKAR TERHADAP IMPOR KEDELAI INDONESIA TAHUN 2011-2020 - Inas Khairunisa (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2022)
Indonesia is the 11th largest soybean consuming country in the world at 3 million tons after China, America, Argentina, and Brazil. The increasing demand for soybeans in the country is due to the increasing population and demand for soybeans. However, it is not balanced with soybean reserves that farmers are capable of producing, so imports are the way out. In addition to low soybean production, the price of imported soybeans and the exchange rate of the USD against the Rupiah also affected Indonesia's soybean imports. This study aims to determine the effect of soybean production, imported soybean prices, and exchange rates on soybean imports in 2011-2020. This type of research is a quantitative study with a sample of 40 quarterly data from 2011-2020. The research method used is multiple linear regression with the ordinary least square model. The results of this study show that soybean production, imported soybean prices, and exchange rates simultaneously have a significant effect on soybean imports. Partially soybean production and imported soybean prices each had a significant negative effect on soybean imports, while the exchange rate did not have a significant effect on Indonesia's soybean imports in 2011-2020.